Mycorrhizal Influence on Nutrient Uptake of Citrus Exposed to Drought Stress - Wu, Qiang-Sheng; Ying-Ning, Zou (2009)
The study evaluated the effect of arbuscular mycorrhizal (AM) fungi on growth and nutrient uptake of trifoliate orange (Poncirus trifoliata) exposed to drought stress. The experiment was carried out using a randomized block design with six replications. The factors studied included application and nonapplication of Glomus versiforme and two levels of drought stress (stress and without stress). Drought stress significantly reduced AM colonization. Mycorrhizal seedlings exhibited greater growth characteristics (fresh and dry weights and leaf area) compared with non-AM seedlings under drought stress and non-drought stress conditions. Concentrations of P, K and Ca in the leaves and concentrations of P, Ca and Fe in the roots were higher in AM than in non-AM seedlings subjected to either non-drought stress or drought stress conditions. AM colonization also increased leaf concentrations of Fe and Zn and root concentrations of K and Mg in seedlings under stress conditions. Mycorrhizal effect responses to N, P, K, Ca, Fe, Mn and Zn were higher under stress than under non-stress conditions. The improved nutrient uptake in colonized seedlings demonstrates the potential of AM symbiosis to enhance drought resistance in citrus.
Keywords: Mycorrhizal fungi